MYSTICISM AS A FORM OF REVELATION - Wayne Teasdale, (Journal of Dharma, 2020)
Mysticism has often been a thorny issue in the history of Western Consciousness, unlike the East where it is the norm. It has always been regarded with a great deal of suspicion in the Church. This is also true, and to a greater degree, in Islam and Judaism. For in orthodox Islam, dominated as it always has been by the theologians and its extreme transcendent orientation, there has been unremitting hostility to Sufism, Islam's very striking school of mysticism. Likewise, in Judaism, there has always been caution, as the Jews have been careful to guard the transcendence of God.